Asymmetrical Conversations : Contestations, Circumventions, and the Blurring of Therapeutic Boundaries - Harish Naraindas, Johannes Quack (Berghahn Books, 2014)
This series in medical anthropology will publish monographs and collected essays on indigenous (so-called traditional) medical knowledge and practice, alternative and complementary medicine, and ethnobiological studies that relate to health and illness. The emphasis of the series is on the way indigenous epistemologies inform healing, against a background of comparison with other practices, and in recognition of the fluidity between them.